Dampak Konseling Apoteker, Ketersediaan Obat, Dan Kualitas Pelayanan Kefarmasian Terhadap Kepuasan Dan Loyalitas Pasien - Dwi Aryanti, Anindita; Kumala, Shirly; Ramadaniati, Hesty Utami (Jurnal Ners, 2024)
The increase of hospitals in DKI Jakarta from 2018-2020 was followed by increased competition between hospitals, Kartini Hospital need to develop strategies to increase patient satisfaction and loyalty to compete with other hospitals. The purpose of this study to analys pharmacist counseling, availability of medication, and quality of pharmaceutical services to increase patient satisfaction and its impact on patient loyalty. The design in this reasearch was an analytic observational study with a cross-sectional. The sample of this study were patients who had received counseling services. Data analysis using questionary that had been tested for validity and reliability, as well as secondary data is measurement of Pharmacy Quality from Komite Mutu Rumah Sakit . Analysis methods with Structural Equation Modeling (SEM) using LISREL 8.8 software. The results of this study concluded that pharmacist counseling, availability of medication, and quality of pharmaceutical services could increase patient satisfaction of 47% (R2 = 0.4678). Pharmacist counseling, availability of medication, and quality of pharmaceutical services and patient satisfaction also have an impact on patient loyalty with a contribution of 52% (R2 = 0.5204).